Trastorno de ansiedad generalizada y su repercusión en el rendimiento deportivo en un adolescente - Smith Espinoza, Patricio Martin (2019)
At present, the Generalized Anxiety Disorder (GAD) is one of the most prevalent within society, causing deterioration in the quality of life of the individual, in the present case study it is inquired about the repercussions of GAD in a adolescent attended in the Sports Federation of the Rivers, who expressed feelings of frustration by decreasing his athletic performance, excessive sweating, palpitations, stomach discomfort, ruling out the federation doctor, some organic cause. Interviews were conducted, using instruments such as; evaluation sheet, clinical history, test to measure qualitatively the levels of anxiety of the adolescent, the data collected in the medical history, family psychopathological history, and irruption of the psychopathological picture were analyzed. For the intervention of the patient, a therapeutic scheme of cognitive behavioral cutting is developed, in order to restructure the patient's deteriorated cognition, reinsert it into their social life, reduce disproportionate physiological manifestations